Multidrug-Resistant Bacteria in Hospital Wastewater of the Korle Bu Teaching Hospital in Accra, Ghana - Daisy S Addae-Nuku; Fleischer CN Kotey; Nicholas TKD Dayie; Mary-Magdalene Osei; Edem MA Tette; Philip Debrah; Eric S Donkor (SAGE Publishing, 2022)
Background: Antimicrobial resistance (AMR) is one of the top 10 public health threats. One approach to tackling the AMR menace could involve expanding the range of AMR surveillance domains to include hospital wastewater (HWW), a domain that has largely been overlooked by researchers. Aim: To evaluate the occurrence of multidrug-resistant bacteria in hospital wastewater of the Korle Bu Teaching Hospital (KBTH). Methodology: This was a longitudinal study involving 288 HWW samples consecutively collected across 12 weeks from the pool of wastewater emanating from 2 critical care units of KBTH-The Child Health Unit and the Maternity Unit-on Mondays and Thursdays, each week. The samples were cultured for bacteria, which were identified using the Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) technique and subjected to antimicrobial susceptibility testing via the Kirby-Bauer method. Results: In total, 294 bacteria of 23 different types, all being Gram-negative, were isolated from the 288 samples. The predominant ones were Escherichia coli (30.6%, n = 90), Klebsiella pneumoniae (11.2%, n = 33), Citrobacter freundii (10.9%, n = 32), Alcaligenes faecalis (5.8%, n = 17), and Pseudomonas mendocina (5.4%, n = 16). The prevalence of multidrug resistance among the isolates was 55.4% (n = 163). Moreover, the prevalence of extended-spectrum beta-lactamase (ESBL) producers was 15.6% (n = 46). E. coli accounted for the most ESBL-producing organisms (28.9%, n = 26). Conclusion: The wastewater generated by the Maternity and Child Health Units of KBTH harbored a wide range of multidrug resistant bacteria, with a good proportion of these being ESBL producers, and the predominant one being E. coli . The study thus identifies the wastewater of KBTH as an important source of multidrug resistant organisms, and underscores the significance of appropriate treatment of wastewater of the hospital and other clinical, and related settings prior to its discharge.